Perubahan pola pembelajaran PKn yang tekstual ke pola kontekstual (CTL) - Edi Suhartono (Jurnal Teori dan Praksis Pembelajaran IPS, 2018)
The development of science and technology has brought great influence to educational technology which further influences learning technology and ultimately to the patterns of learning from conventional/ traditional (textual and teacher only learning) patterns to transition patterns (semi textual and teacher together media) and finally to modern patterns (contextual and media as learning resources). This is very influential on the pattern of learning Civic that is conventional/traditional textual to contextual learning patterns. The current reality in Indonesia is that civic learning is still dominated by conventional systems, so that the application of contextualized oriented learning is still far from expectations, as evidenced by the still serious learning problem, where most students can not relate what they have learned and applications in his current and future life. This occurs because the lesson of civics is less related to the material with the reality of student life, not contextual, consequently civics fails in carrying out its mission to develop civics competence namely civics knowledge, civics disposition and citizenship skills. In carrying the contextualized oriented civics learning, conventional learning system in schools is increasingly believed to be a system that is not effective anymore and resulted in learning Civics felt less meaningful for students To solve the problem of learning civics less meaningful, it is necessary to use contextual teaching approach learning) as one effective alternative. The application of contextual learning is an urgent need to solve the civic problems.DOI: 10.17977/um022v3i12018p001